Long-distance passive dispersal in microscopic aquatic animals - Fontaneto, Diego (Mov Ecol, 2019)
Given their dormancy capability (long-term resistant stages) and their ability to colonise and reproduce, microscopic aquatic animals have been suggested having cosmopolitan distribution. Their dormant stages may be continuously moved by mobile elements through the entire planet to any suitable habitat, preventing the formation of biogeographical patterns. In this review, I will go through the evidence we have on the most common microscopic aquatic animals, namely nematodes, rotifers, and tardigrades, for each of the assumptions allowing long-distance dispersal (dormancy, viability, and reproduction) and all the evidence we have for transportation, directly from surveys of dispersing stages, and indirectly from the outcome of successful dispersal in biogeographical and phylogeographical studies. The current knowledge reveals biogeographical patterns also for microscopic organisms, with species-specific differences in ecological features that make some taxa indeed cosmopolitan with the potential for long-distance dispersal, but others with restricted geographic distributions.